Pengaruh Infrastruktur terhadap PDRB Kawasan Timur Indonesia Tahun 2014 – 2022 - Mahardika, Gita Sukma Andini; Hayati, Banatul (JURNAL ECONOMINA, 2024)
Economic growth according to Solow Swan's theory is influenced by the factors of capital accumulation, labor, and technological progress. Infrastructure is a form of physical capital that can increase economic activity. During the government of President Joko Widodo, there is the concept of “Nawacita” which in its agenda has points to increase people's productivity and competitiveness in the international market and points to build Indonesia from the periphery by strengthening regions and villages within the framework of a unitary state. The real condition that occurs today is the phenomenon of the development gap. In order to implement this agenda, the government divides Indonesia into the Western Region and the Eastern Region of Indonesia. Eastern Indonesia is considered to be underdeveloped because if seen from the contribution of KTI to the National GRDP, it only contributes less than 25 percent. The purpose of this study is how infrastructure affects the 17 provinces of Eastern Indonesia. The study uses secondary data with panel data regression analysis with the Fixed Effect Model (FEM). The variables used are economic growth represented by GRDP as the dependent variable and road infrastructure, electricity infrastructure, TPAK, number of internet users as independent variables. The results showed that the variables of electricity infrastructure and the number of internet users had a significant positive effect on economic growth while the variables of road infrastructure and TPAK had no significant effect on economic growth.